Career Preparation Menghadapi Kecemasan Dunia Kerja pada Mahasiswa - Ika Yuliana; Restu Alpiansah; Aryan Agus Pratama; Isra Dewi Kuntary Ibrahim (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
The objective of this activity is to facilitate students in developing a comprehensive understanding of their chosen professional path, specifically in banking. This exercise is specifically designed for students enrolled in the Management Study Programme. The service employs a peer mentoring methodology encompassing preparation, design, implementation, and evaluation stages. This technique was selected due to its appropriateness in facilitating students' acquisition of new knowledge through interactions with those possessing greater expertise. This activity encompasses a comprehensive examination of several aspects related to the banking industry. The topics covered include the precise delineation of a bank, a preliminary overview of bankers, the prerequisites that necessitate fulfillment to pursue a career as a banker, the potential trajectories within the banking profession, and lastly, valuable insights and strategies to facilitate success in the pursuit of a banking career. Through this service activity, students are provided with a comprehensive understanding of their intended job. Subsequently, those aspiring to pursue a career in the banking industry can adequately equip themselves with the necessary prerequisites.